(untitled) (Palíndromo, 2026)
The article examines the reconfiguration of the sublime in the Anthropocene, shifting it from the tradition that linked it to the grandeur of nature to its positioning within the consequences of human action on the planet. The objective is to understand how contemporary artworks evoke the experience of the sublime in a context marked by environmental devastation. The methodology is based on a critical review of the aesthetic tradition of the sublime, as well as contemporary debates on climate crisis and historical responsibility, supporting the idea that current awe emerges from awareness of human-induced devastation. The analysis focuses on Siluetas (1973–81) by Ana Mendieta and Genocide of the Yanomami: Death of Brazil (1989) by Claudia Andujar, combining theoretical discussion with formal interpretation of the works. As a result, it is observed that in Mendieta, the inscription of the body into the earth produces an immanent sublime, characterized by belonging and vulnerability; in Andujar, the repeated imagery of violence establishes a tragic sublime that confronts the viewer with the ethical scale of catastrophe. It is concluded that, in the context of the Anthropocene, the sublime in these artistic practices shifts from the contemplation of grand nature to a critical experience linked to awareness of environmental disruptions and inequalities produced by human action, becoming a category capable of revealing tensions among humanity, environment, and power.